The Influence of Local Cultural Learning on Critical Thinking Skills of Elementary School Students in South Lampung - Dominikus Didi Woda; Muhammad Sofian Hadi (Bulletin of Science Education, 2025)
Learning about local culture plays a significant role in developing critical thinking skills among elementary school students in South Lampung. By integrating local wisdom into daily learning activities, students are exposed to the values embedded in local customs and traditional arts, which encourage them to analyze, evaluate, and reflect on information in a logical and in-depth manner. This study employed a quasi-experimental design to test the causal relationship between local culture-based learning and the enhancement of students’ critical thinking abilities. Based on the analysis results, the calculated t-value (2.654) exceeded the t-table value (0.67986) at a 5% significance level. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted, indicating that learning about local culture has a positive and significant effect on students’ critical thinking skills. This study contributes to educational practice by demonstrating that integrating local cultural content into the elementary school curriculum can effectively foster critical thinking development. It provides empirical evidence supporting the inclusion of culturally relevant learning materials to promote cognitive and cultural growth simultaneously